Dynamiczne Ugięcia Krótkiego Mostu Kolejowego - Boblewski, J. (Engineering Transactions, 1973)
The paper contains an information concerning the program BBL-3 for a ZAM-2 digital computer which makes it possible to solve the differential equation of vibration of a beam produced by a vehicle moving on that beam at a constant velocity. The rigidity of the beam is assumed to be the load acts in the plane of symmetry of the beam, its axis is rectilinear before constant, deformation, and the mass of the vehicle cannot be disregarded in comparison with the mass of the beam. The paper presents the method of derivation of the set of differential equations and the scheme of its solution under the assumption that the beam may be considered as a system with one degree of freedom.